Recent advances in phlebotomine sand fly research related to leishmaniasis control - Bates, Paul A; Depaquit, Jerôme; Galati, Eunice AB; Kamhawi, Shaden; Maroli, Michele; McDowell, Mary Ann; Picado, Albert; Ready, Paul D; Salomón, O Daniel; Shaw, Jeffrey J; Traub-Csekö, Yara M; Warburg, Alon (Parasites & vectors, 2015)
Phlebotomine sand flies are the subject of much research because of the role of their females as the only proven natural vectors of Leishmania species, the parasitic protozoans that are the causative agents of the neglected tropical disease leishmaniasis. Activity in this field was highlighted by the eighth International Symposium on Phlebotomine Sand flies (ISOPS) held in September 2014, which prompted this review focusing on vector control. Topics reviewed include: Taxonomy and phylogenetics, Vector competence, Genetics, genomics and transcriptomics, Eco-epidemiology, and Vector control. Research on sand flies as leishmaniasis vectors has revealed a diverse array of zoonotic and anthroponotic transmission cycles, mostly in subtropical and tropical regions of Africa, Asia and Latin America, but also in Mediterranean Europe. The challenge is to progress beyond descriptive eco-epidemiology, in order to separate vectors of biomedical importance from the sand fly species that are competent vectors but lack the vectorial capacity to cause much human disease. Transmission modelling is required to identify the vectors that are a public health priority, the ones that must be controlled as part of the integrated control of leishmaniasis. Effective modelling of transmission will require the use of entomological indices more precise than those usually reported in the leishmaniasis literature.